IMPLEMENTASI PENDIDIKAN KARAKTER CINTA TANAH AIR MELALUI PEMBELAJARAN IPS DI MI MA’ARIF NU 1 PANUSUPAN - Mutaqin, Mutaqin; Ningsih, Tutuk (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Character education of love for the country needs to be grown in the soul of every learner, because students are an investment in the nation that will be responsible for bringing Indonesia to a better direction. Character education can be instilled through social studies learning and impact on behaviour change towards the desired after social studies learning activities. The method used in this research is the type of field research, using a descriptive qualitative approach. The research subjects were students and teachers of grade V MI Ma'arif NU 1 Panusupan. Data collection was done by interview, observation, and documentation. Researchers conducted data analysis after all data were collected. There are 3 stages of data analysis used by researchers, namely through data reduction, data presentation and conclusion drawing. The results of the study state that the implementation of patriotism character education is carried out to fortify students from external threats that enter through culture. In the implementation, teachers play a very important role in carrying out, teaching, modelling and supervising the habituation of the implementation of patriotism character education. This is done by the teacher by emphasising the value of the character of loving the country to students, giving examples of behaviour to students and inviting students to instill the character value of loving the country in each learner.